The Political Economy of Fisheries Development During Joko Widodo’s Regime - Nasution, Anta Maulana; Wicaksono, Viga Ananda (Magister Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
The article discusses the political economy of fisheries development in Indonesia and its dynamics during Joko Widodo's regime. The development of the fisheries sector, particularly marine fisheries, has faced ups and downs since Indonesia's independence. During the New Order era, fisheries development depended on foreign investment and international aid, which on several occasions has driven severe conditions in depleted fish stocks and the marginalization of small-scale fishermen. The fisheries sector began to be measured politically after the reform period when Indonesia established the Department/Ministry of Marine Affairs and Fisheries. Even so, the direction of fisheries development has not met its consistency. When Joko Widodo served as president, he created a big vision for maritime development, namely